Effects of antidiabetic drugs on bone metabolism - Padilla Apuntate Nuria; Puerto Cabeza Carmen G.; Gallego Royo Alba; Goñi Ros Nuria; Abadía Molina Claudia; Acha Pérez Javier; Calmarza Pilar (Advances in Laboratory Medicine, 2024)
The prevalence of diabetes mellitus type 2 (DMT2) is increasing exponentially worldwide. DMT2 patients have been found to be at a higher risk for bone fractures than the healthy population. Hence, improving our understanding of the impact of antidiabetic drugs on bone metabolism is crucial.